Identification of a missense mutation (G261D) in the alpha- galactosidase A gene in a Libyan family with Fabry disease - Refaat Tabagh (The Libyan Journal of Science, 2022)
Background: Fabry disease (FD) is a rare X-linked genetic lysosomal storage disease with a defect in the activity of the alpha-galactosidase A (α- GLA) lysosomal hydrolase enzyme, which breaks down globotriaosylceramide in lysosomes. Fabry disease is characterized by many unique mutations. Molecular diagnosis is essential for identifying heterozygosity in patients with Fabry disease. Case-series: This case series includes two Libyan brothers with classic Fabry disease predominantly with nephropathy and on hemodialysis, and their sister, who had mainly proteinuria. They were studied clinically and genetically. Only patient 1 had renal and cardiac involvement. None of the patients had enzyme replacement therapy. This study aimed to identify the mutation in the alpha-galactosidase A gene in these patients. Methods. DNA samples from patients with FD at age 30 and 45 years were screened by DNA- PCR and direct DNA sequence analysis to search for genetic sequence variations in the α-GLA gene. Results: Missense point mutation c.782G>A, p. G261D in exon five of the alpha-galactosidase A gene was detected in the three patients. Conclusion: This work highlights that there is a genotype-phenotype association between FD clinical findings and mutations in the α-GLA gene, which may be useful in the genetic counseling of FD patients.